Biomimetic Extreme‐Temperature‐ and Environment‐Adaptable Hydrogels. Issue 17 (1st August 2019) - Zhou, Dan; Chen, Fan; Handschuh‐Wang, Stephan; Gan, Tiansheng; Zhou, Xiaohu; Zhou, Xuechang
Abstract: Recently, temperature‐resistant hydrogels, hydrogels which are freezing‐ and dehydration‐resistant, have garnered considerable attention in the scientific community as they extend the rage of application of hydrogels to arid and/or cold environments. Besides, these hydrogels exhibit tunable conductivity and mechanical performance while offering excellent biocompatibility and flexibility, making them interesting candidates for flexible and wearable electronics and (bio)sensors. Several biomimetic strategies were developed to fabricate anti‐freezing and anti‐dehydration hydrogels with a diversity of merits, such as high strain resistance and conductivity, even at sub‐zero temperatures, and employed as (bio)sensors, electrodes, and energy‐storage devices. This review summarizes the recent advances in the preparation and application of temperature‐resistant hydrogels, indicates issues of the state‐of‐the‐art hydrogels, and offers potential future research directions. Abstract : Temperature‐resistant hydrogels that can withstand cold and arid environments without degradation of their properties can be fabricated by a variety of strategies. Here, recent fabrication routes for anti‐freezing, non‐drying hydrogels are reviewed. The merits and drawbacks of the materials are discussed and possible applications in flexible electronics are highlighted. The authors also point out future challenges to elucidate the great potential of this juvenile research area.